The Effects of Cross-Legged Sitting on the Lower Limb Muscles and Body Balance and the Implications in Rehabilitation - Hadeel Alsirhani; Abdullah Alzahrani; Graham Arnold; Weijie Wang (Applied Sciences)
Background: Although a cross-legged sitting (CLS) posture has been commonly practiced as a daily activity, particularly in Arabic, Middle Eastern, and Asian societies, there is no medical study focusing on the effects of cross-legged sitting on body balance and muscular strength. Therefore, this study aimed to investigate the effect of CLS on lower extremity muscular strength, muscular electrical activity, and body balance. Methods: Thirty healthy volunteers participated in this research study by performing CLS for a 20 min duration. The balance tests included a static test, i.e., a single-leg-standing posture with eyes closed, to assess if the centre of the pelvis and centre of the shoulders (CoS) moved, and a dynamic test, i.e., four-square-returning, to assess if the moving speed changed. Regarding the muscular assessment, the electrical activity was assessed depending on the maximal value of activation and rooted mean of squared values, while the muscular strength was assessed according to the maximum force by the lower limbs using a force sensor. The balance and muscular results were statistically compared before and after CLS. Results: The duration of the static balance after CLS decreased by an average of 2.5 s, or approximately 15.64%, compared to before CLS (p < 0.05 *). Further, the Centre of Pelvis moved greater distances in the medial–lateral direction after CLS compared to before, but CoS was not significantly changed in the static balance test. However, in the dynamic balance test, the duration significantly decreased by 0.2 s, or approximately 8.5%, after CLS compared to before, meaning that dynamic balance ability improved. Considering the muscle results, only the lateral gastrocnemius muscle was noticeably electrically activated after CLS, while the hip extensor and knee flexor muscles became significantly stronger after CLS compared to before, roughly by about 14%, and the ankle plantar flexor maximum force increased noticeably, by about 4%, after CLS. Conclusions: CLS had a positive impact on the dynamic balance; the strength of the hip extensor, knee flexor, and ankle plantar flexion; and all lower limb muscles, in terms of electrical stimulation, except for the lateral gastrocnemius post-CLS compared to pre-CLS. Therefore, CLS can be safely included in one’s daily routine and in any rehabilitation programme, except for patients who are suffering from static balance disturbance. Although this posture is commonly used in many societies, because this is the first study focused on the impact of CLS on body balance and muscular status, the results would supply knowledge and new understanding, as well as provide clear insight for sitting posture research.